Prune belly syndrome: a 31 year experience at the Chris Hani Baragwanath Academic Hospital, South Africa - Leahy, Shannon Dale (My University, 2017)
Background: PBS is a rare congenital disorder with a triad of signs: absent abdominal wall musculature, urinary tract malformations, cryptorchidism. Objectives: Describe the patient profile, management, and outcome of patients attending the Paediatric Nephrology clinic at Chris Hani Baragwanath Academic Hospital. Methods: Retrospective descriptive record review. Results: 44 patient files were analysed. Median duration of follow up: 24 months (1.7–130). Median age at presentation was 5.5 days (1–730). Associated conditions included: urological 48%, orthopaedic 11%, congenital heart disease 7%, gastrointestinal 4.5%. Medical management included prophylactic antibiotics and intermittent bladder catheterisation. Surgical management included abdominoplasty with orchidopexy (3 years) and circumcision (7.7 years). Patients over the age of 2 years had a better overall outcome. There was a high default rate of 57%. Conclusion: Patient profile and management is comparable to other reported series. Deterioration in renal function to ESRD was observed less in this review possibly due to the high default rate.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Paediatrics Johannesburg, 2017
Keywords: Prune Belly Syndrome; Pediatrics